Review of certain lectotype designations in Hinda (Coleoptera, Coccinellidae, Hyperaspinae), primarily those deposited in Museum für Naturkunde der Humboldt-Universität, Berlin, Germany - de Almeida, Lúcia Massutti; Milléo, Julianne; Gordon, Robert D. (Zootaxa, 2007)
Type specimens of Hinda in the Zoologisches Museum der Humboldt Universität, Berlin, Germany, and other institutions were studied. Lectotypes and paralectotypes of Hinda quindecimmaculata Weise (1895) and of H. modesta Weise (1910) are designated. An error by Almeida and Milléo (2000) in designating a lectotype for Hinda regularis Erichson (1847) is corrected. Known geographical distributions of H. modesta and H. humerata are expanded.